Eksistensi Hukuman Mati terhadap Kasus Pembunuhan Perspektif Hukum Pidana Indonesia dan Hukum Islam - Nurul Amalia Syahrullah Yulianto; Nur Mohamad Kasim; Erman I. Kasim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
The death penalty is one of the issues that has pro and con views. This paper contains behaviours that cause death penalty sanctions and the application of the death penalty in Indonesia based on Indonesian criminal law and Islamic law. This paper is a normative legal research. The determination of this type of research is based on the consideration that the orientation of this study is more intended to find legal rules, legal principles and legal doctrines in order to answer the legal issues at hand. The results show that the death penalty is not in line with respect for human rights that must be respected and protected, while in Islamic teachings, if it occurs, the term qisas (retaliation in kind) is known, namely if someone kills, then the reply is also murder, but on the other hand the term forgiveness from the victim's family is known, so qisas is not applied.